Existencial Poetics in the 19th Century Latin America - Edwin Murillo (Revista de Filología y Lingüística de la Universidad de Costa Rica, 2019)
Typically, the origin story of Existentialism has depicted Latin America’s contributions as subsequent and tributary to its European counterpart. Nevertheless, a select few critics have approached this history in Hispanic America from a chronologically inclusive perspective, by calling attention to an Existential Poetics in modernismo. This article expands the borders of Existential Poetics to fashion a Latin American literary imaginary. Given the work already done on Rubén Darío and José Martí, both of whom have been studied independently, my analysis will be collective, favoring philopoetic works by Manuel Gutiérrez Nájera, Julián del Casal, José Asunción Silva, and João Cruz e Sousa. The purpose of examining Hispanic-American poets in conjunction with a Brazilian is to accentuate the Pan-American quality of this Existentialism avant la lettre.  As I will discuss, all these poems deal with a crisis of irrelevance and overtly question being in the world, classic motifs of Existentialism. Together, these poems allow for the synchronized inclusion of Latin American voices to the universal history of Existentialism, an approached not explicitly carried out by most philosophical and literary historiographers.